Insertion of the superior head of the lateral pterigoid muscle in the human fetuses - Altruda Filho, Luiz; Alves, Nilton [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2006)
The lateral pterygoid muscle, more specifically its superior head, as we know, is closely related to the temporomandibular joint (TMJ). Particularly in children, in contrast with what was observed in adults, these joints have been rarely studied, by the anatomic functional aspect, little knowing about its functions in the embryonic and fetal periods. We used, in this work, 12 fetuses ranging in age from 16 to 39 weeks of intrauterine life, where we observed that the superior head of the lateral pterygoid muscle is inserted in the disc and in the articular capsule, in all age groups studied, and also, that the fibers and the thickness of the articular disc is, as well as the articular capsule suffer modifications in accordance with the period of development. © 2007 Sociedad Chilena de Anatom•br>.
Keywords: Lateral pterygoid muscle; Temporomandibular joint; Temporomandibular joint disc